Introduction: between human history and the history of nature (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The paper presents a quick historiographical overview of the environmental historiography of the Middle Ages. In particular, it examines the relationship between the data provided by documentary sources and those provided by the natural sciences that study the past ('palaeosciences'), retracing their use during the last hundred years. The dialogue between historians and natural scientists presents great difficulties, but it also offers great opportunities and is increasingly necessary to understand our past.
Keywords: Environmental history; palaeosciences; Middle Ages